Effect of two management systems and mineral feeding on age at puberty in Nili-Ravi buffalo heifers - Bodla, Muhammad Tariq; Anwar, Muhammad; Ahmad, Ejaz; Naseer, Zahid; Ahsan, Umair (Buffalo Bulletin, 2017)
The data of buffalo heifers reared in pasture (N=213) and stall feeding system (N=274) were collected to determine the age at puberty and seasonality in breeding behavior through a survey study. The results revealed that the age at puberty and seasonality in breeding behavior was lower in heifer reared in pasture compared to stall feeding system. To determine the effect of mineral supplementation on estrus response, thirty five buffalo heifers were divided into two groups; MIN and CTL. The MIN (N=20) group were fed with mineral mixture (100 grams/day/heifer) for four weeks. Whereas, CTL group (N=15) did not receive any mineral supplementation. Mineral supplementation enhanced estrus response in MIN compared to CTL heifers (65% versus 33%). In conclusion, the age at puberty and seasonality in breeding is less in heifers of pasture system. Furthermore, mineral feeding is helpful to induce estrus in heifers that had achieved average age of puberty.